Mutu Permen Soba Rumput Laut (Kappaphycus alvarezii) Pada Lama Pemasakan Yang Berbeda - Kalaka, Sri Rahayu; Yusuf, Nikmawatisusanti; Ahmad, Nurain (Universitas Negeri Gorontalo, 2025)
This research aims to determine the hedonic quality and crude fiber of seaweed buckwheat candy. This research used three levels of treatment, namely 1 hour, 1.5 hours and 2 hours of cooking. The parameters tested include hedonic quality and crude fiber. The research method used is the experimental method. The data analysis used was Kruskall waliis and Completely Randomized Design (CRD), Duncan continued testing with the help of SPSS 25. The results showed that seaweed buckwheat candy with different cooking times, namely 1 hour, 1.5 hours and 2 hours had a significant effect on taste, the aroma and texture of the candy produced, while the crude fiber content had no significant effect. Organoleptically, the hedonic quality of seaweed buckwheat candy has a good taste, coconut milk and brown sugar have a strong taste, have a slight seaweed taste to very good, coconut milk and strong brown sugar do not have a seaweed taste; buckwheat candy has a strong coconut milk and brown sugar scent, not a seaweed scent to a very strong coconut milk and brown sugar scent, not a seaweed scent; the texture of the candy is soft to soft, slightly hard. Seaweed buckwheat candy crude fiber ranges from 1.51% - 1.71%.